Pengaruh Metode Hybrid Learning terhadap Minat Belajar Mahasiswa Universitas Indraprasta PGRI Jakarta - Elmas, Nur Fatimah; Adi, Tony Margiyanto (Neolectura, 2023)
The purpose of this study was to determine the effect of the hybrid learning method on the learning interest of students of the economic education study program in the morning regular class class of 2019 at Indraprasta University PGRI Jakarta. The research method used in this study is a quantitative approach. This type of research is correlational research. Correlational research is a study to determine the relationship and level of relationship between two or more variables without any attempt to influence these variables so that there is no variable manipulation (Faenkel and Wallen, 2008:382). The results obtained are a correlation value or (R) of 0.43 with a moderate level of relationship so that the contribution of the hybrid learning method to student learning interest is 18.49% and the rest is influenced by other variables not examined in this study. It can be concluded that the hybrid learning method can affect student learning interest even though it is not significant.